Bridging the Gap: Augmented Reality for Math Education among Saudi Deaf Students - Yusra Zaki Aboud; Rommel Al Ali (Decision Making: Applications in Management and Engineering, 2025)
Mathematics is often considered to be an important language, but for deaf students who are facing communication barriers, it becomes a tough language to understand the concept, even though a basic language. Therefore, to address this issue, the study aimed to investigate the augmented reality effectiveness of the mathematics education of deaf elementary students in Saudi Arabia. Using a pretest and posttest paired sample t-test; researchers employed the quantitative experimental research design. A sample of Al-Amel Institute for Deaf Students in Al-Ahsa Province 60 students selected, who were enrolled in a class on the concept of circles chosen for the study, divided into two groups: an experimental group that received mathematics education by using AR and a control group that traditionally received education. The results revealed a significant improvement in posttest scores of the experimental group as compared to the control group, indicating that augmented reality has a positive impact on mathematics learning of deaf students in Saudi Arabia. The findings suggest that AR can be an effective tool in enhancing DHH students’ mathematics learning because the scores showed significant improvement in the sample t-test for understanding geometry. Positive feedback from participants further highlights the potential of AR to revolutionize math education for deaf students. Therefore, AR tools must be incorporated into the special education curriculum that facilitate their visual and interactive learning experience